Metabolic benefit of intermittent fasting among type 2 diabetes mellitus patients: a systematic review - Mohamed Nor, Noraishah; Mohd Fauzi, Nur Farhanim; Afandi, Aflah (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
Introduction: The global economic burden is escalating due to the growing prevalence of Type 2 Diabetes Mellitus (T2DM). Maintaining T2DM remission and substantial weight loss is essential, and this review provides extensive evidence about the metabolic benefit of Intermittent Fasting (IF). Methods: The Preferred Reporting Items for Systematic Study and Meta-Analysis (PRISMA) procedure was utilized in this review. The search yielded 628 articles from the Scopus, ProQuest, PubMed, and Cochrane Library databases. The final 13 studies showed that IF can benefit individuals with T2DM. Results: Weight loss was more visible, while HbA1c and blood glucose levels could be improved. Time-restricted fasting (16 to 20 hours daily for at least five days a week) is the most suitable and feasible IF regimen for T2DM patients. Conclusion: IF appears to be a safe and effective strategy for improving glycemic control and promoting weight loss in patients with T2DM. However, careful monitoring of the types, quantities, and timing of food intake remains crucial to maximize its long-term benefits.